Pelaksanaan Pemekaran Daerah Kota Sungai Penuh dari Kabupaten Kerinci dan Dampaknya terhadap Wilayah Pinggiran Kota Sungai Penuh - Adryan Adryan; Erwin Erwin; Jafrinur Jafrinur (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
Law Number 32 Year 2004 on Regional Government article 4 stated that the formation of regions could be in the form of merging or splitting one area into two or more regions. The implementation of the splitting or extension will effect the improvement of community welfare, acceleration of public services, and management of regional potential. This study is aimed (1) to describe the consideration of Sungai Penuh City extension from Kerinci Regency; (2) to analyze the influences of city extension in increasing economic growth and potential development of Sungai Penuh City Area; and (3) to understand the impact of city extension on development of Sungai Penuh periphery area. This study conducts case study research with using qualitative and quantitative method, and determines informant using purposive sampling technique. Qualitative analysis is used to achieve the first and the third research purpose, and quantitative analysis is used to achieve the second research purpose. Results stated that the implementation of Sungai Penuh City extension is implemented by considering physical condition, regional function, economy, and social community. Economic growth of Sungai Penuh City after city extension increased 3.13% during 2010 to 2016. The economic growth was also supported by the increase of Human Development Index. The trade sector becomes a potential sector to be developed in Sungai Penuh City. City economic growth has an impact on development of its periphery area through the availability and accessibility of educational, health and agricultural infrastructure.